PENGARUH MOTIVASI KERJA DAN LOYALITAS KERJA TERHADAP KINERJA PEGAWAI PADA BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN GIANYAR - Ni Putu Eka Rosi Febby Diana; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Realizing how important work motivation and work loyalty are in an effort to improve employee performance, the General Section of the Gianyar Regency Regional Secretariat with all its limitations tries to implement the program. There are concerns and findings regarding the problem of work motivation and work loyalty in an effort to improve and improve employee performance in accordance with the purpose of this study to determine the effect of work motivation and work loyalty on employee performance at the General Section of the Regional Secretariat of Gianyar Regency. The sampling technique used the saturated sampling technique with a total sample of 43 employees. Data analysis in this study uses Multiple Linear Regression Analysis which data processing is assisted by using the IBM SPSS Statistic 25 application. The results showed that 1) Work motivation had a positive and significant effect on employee performance in the General Section of the Gianyar Regency Regional Secretariat 2) Work loyalty had a positive and significant impact on employee performance in the General Section of the Gianyar Regency Regional Secretariat. Suggestions that can be given to agencies include: to the leadership of the General Section of the Gianyar Regency Regional Secretariat providing opportunities for employees to attend training and seminars, create more working relationships between employees and superiors and fellow employees in one section or with other sections, in Placement of employees should be adjusted between positions with employee education and pay attention to the accuracy of employee work by carrying out existing work standards / SOPs properly and firmly.